2011
DOI: 10.1109/tvcg.2011.224
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Touch Table System for Medical Visualization: Application to Orthopedic Surgery Planning

Abstract: Medical imaging plays a central role in a vast range of healthcare practices. The usefulness of 3D visualizations has been demonstrated for many types of treatment planning. Nevertheless, full access to 3D renderings outside of the radiology department is still scarce even for many image-centric specialties. Our work stems from the hypothesis that this under-utilization is partly due to existing visualization systems not taking the prerequisites of this application domain fully into account. We have developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 18 publications
2
50
0
1
Order By: Relevance
“…Sultanum et al not only base their work on observational sessions with the target users [73] but also conducted an evaluation of their final design [74] with domain experts. This last study revealed that, while the participants liked the overall system design with its flexible and fluid data exploration, they too asked for specific precise views such as 2D projections, similar to what was reported by Klein et al [55] and Lundström et al [61]. The systems discussed so far rely on the interaction with 2D projections of the 3D data visualizations-largely due to the interaction problems that arise from the combination of touch input and stereoscopic projection (as discussed in Section 2.2).…”
Section: Fig 16supporting
confidence: 67%
See 3 more Smart Citations
“…Sultanum et al not only base their work on observational sessions with the target users [73] but also conducted an evaluation of their final design [74] with domain experts. This last study revealed that, while the participants liked the overall system design with its flexible and fluid data exploration, they too asked for specific precise views such as 2D projections, similar to what was reported by Klein et al [55] and Lundström et al [61]. The systems discussed so far rely on the interaction with 2D projections of the 3D data visualizations-largely due to the interaction problems that arise from the combination of touch input and stereoscopic projection (as discussed in Section 2.2).…”
Section: Fig 16supporting
confidence: 67%
“…Some types of data, however, inherently favor a horizontal mapping, such as surgery-based medical visualizations. Lundström et al [61] thus use such a horizontal setup to create their virtual surgery (a) Single-user interaction.…”
Section: Systems and Design Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also aimed to identify best possible use for variety of purposes in different domains [39] [40]. These systems are used to investigate the co-located collaborative work [41] and for visualization of 2D/3D digital information [42][43].…”
Section: International Journal On Smart Sensing and Intelligent Systementioning
confidence: 99%